Estudo da cominuição na solubilidade da rocha fosfática Bayóvar - Plotegher, Fábio (2014)
Phosphorus is a vital element for both animals and plants. In recent decades, the population growth boosted the production of food and technologies applied to the crops. The intense use of land for monoculture depletes the soil nutrients rapidly, requiring its replacement with fertilizer. Among the main macronutrients, phosphorus is the least required by plants. However, it is the one that most limits productivity in Brazilian soils, mainly because iron and aluminum ions in the soil immobilize this nutrient. The use of phosphate rocks in crops has been studied in recent years as an attempt to control the release of phosphorus in the soil. The present research aimed at studying the kinetics of phosphate release. Analysis were carried out on samples of milled phosphate rock and synthetic samples of two apatites. The results were compared to the kinetic analysis of a high solubility phosphate fertilizer widely used in the fields. The study was divided in three stages: the physical-chemical characterization of the simple superphosphate fertilizer; the physical-chemical characterization of the phosphate rock; and the characterization of apatite s synthetic phases. The results confirmed that the phosphate fertilizer has a phase already quite soluble in water. Through the calculated kinetic parameters it was observed that with a short milling time it was possible to increase the nutrient release. This study served mainly to determine the conditions of the test and also to confirm that the mechanical activation is one way to increase the solubility of less soluble materials. The results of the Bayóvar rock characterization showed that its major mineral phase is apatite which has a low solubility in water. Solubility tests in citric acid showed increased solubility of the material when increasing the milling time, with top system performance (mill/jar and alumina balls) in 20 minutes. As what happened to the fertilizer, the mechanical activation played a significant role to increase the material solubility, even with the material being little soluble. The mineralogical phase of phosphate is also crucial to the success of the release. To check if the mineralogical phase in fact influences the release kinetics, the isolated phases of two apatites were studied. Hydroxyapatite and fluorapatite samples were synthesized via coprecipitation and the particles were grown by hydrothermal treatment, varying time and temperature. The characterizations showed success in the synthesis of samples via co-precipitation. The results of XRD, SEM and BET also showed that temperature was more influential on the crystal growth than on the changes in its morphology. xii Solubility tests, also with citric acid, showed that indeed the mineralogical phase of phosphate is important and will be decisive in the choice of possible rock or natural phosphates to be used for direct soil fertilization.